The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2022
DOI: 10.3390/nu14030690
|View full text |Cite
|
Sign up to set email alerts
|

Hydrolyzed Proteins and Vegetable Peptides: Anti-Inflammatory Mechanisms in Obesity and Potential Therapeutic Targets

Abstract: Chronic low-grade inflammation is present in overweight and obesity, causing changes in several metabolic pathways. It impairs systemic functioning and positively feeds back the accumulation of more adipose tissue. Studies with hydrolyzed proteins and plant peptides have demonstrated a potential anti-inflammatory and immunomodulatory effect of these peptides. However, it is challenging and necessary to explore the mechanism of action of such molecules because understanding their effects depends on their struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 69 publications
(120 reference statements)
0
7
0
Order By: Relevance
“…In the current study, TNF-α, MCP-1 and TBARS levels were elevated in the CON group, increasing the likelihood that ob / ob mice would develop obesity along with pre-diabetic condition and confirming the anti-obesity effect of MLPH by reducing TNF-α, MCP-1 and TBARS levels, although the mechanism of improvement of adipose tissue by MLPH treatment was not clearly revealed. In obese mice, de-Medeiros et al [ 47 ] found that tiny hydrolyzed proteins and vegetable peptides efficiently reduced inflammatory proteins such as TNF-α and MCP-1. Similarly, the current study found that MLPH containing a short peptide chain could significantly modulate serum levels of adiponectin, TNF-α, MCP-1, and TBARS in ob / ob mice.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, TNF-α, MCP-1 and TBARS levels were elevated in the CON group, increasing the likelihood that ob / ob mice would develop obesity along with pre-diabetic condition and confirming the anti-obesity effect of MLPH by reducing TNF-α, MCP-1 and TBARS levels, although the mechanism of improvement of adipose tissue by MLPH treatment was not clearly revealed. In obese mice, de-Medeiros et al [ 47 ] found that tiny hydrolyzed proteins and vegetable peptides efficiently reduced inflammatory proteins such as TNF-α and MCP-1. Similarly, the current study found that MLPH containing a short peptide chain could significantly modulate serum levels of adiponectin, TNF-α, MCP-1, and TBARS in ob / ob mice.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the rise in inflammatory disorders has prompted the search for proteins and peptides with anti-inflammatory effects [ 92 ]. In this case, one technique is to research possible compounds, such as plant proteins, that have been studied as a source for bioactive peptides with anti-inflammatory activity agents [ 93 ]. Hydrolysates and peptides generated from legumes can have various biological effects, including anti-inflammatory, antioxidant, antihypertensive, anticancer, and immunomodulatory properties [ 6 ].…”
Section: In Vitro and In Vivo Studies On The Antioxidant Ace-inhibito...mentioning
confidence: 99%
“…223 Other recent reviews highlight therapeutic effects of plant-derived peptides towards diabetes and related complications. 224,225 There are known metal-binding amino acid residues, thus it is expected that plant protein-derived peptides have metal-binding capacity. 226 Esfandi et al hydrolyzed oat bran proteins using four proteases, Alcalase, Flavourzyme, papain, and Protamex.…”
Section: Peptidesmentioning
confidence: 99%
“…223 Other recent reviews highlight therapeutic effects of plant-derived peptides towards diabetes and related complications. 224,225…”
Section: Plant-derived With Bioactivity Related To Transition Metal I...mentioning
confidence: 99%